Kawasaki Disease in a Preschooler: A Case Study on Timely Diagnosis and IVIG (Intravenous Immunoglobulin) Intervention - Fitriana Wibowo; Didik Hariyanto; Farid I Hussein (HM Publisher, 2025)
Background: Kawasaki disease (KD) is an acute, systemic vasculitis predominantly affecting young children and represents the leading cause of acquired heart disease in developed nations. Diagnostic challenges, particularly in resource-limited settings like Indonesia, contribute to underdiagnosis and delayed treatment. Case presentation: We report the case of a 3-year-8-month-old Indonesian male who presented with a five-day history of high-grade fever, polymorphous rash, bilateral non-purulent conjunctival injection, oropharyngeal changes (strawberry tongue, dry cracked lips), and unilateral cervical lymphadenopathy. These features fulfilled the classic diagnostic criteria for KD. Laboratory investigations revealed mild normocytic anemia and a markedly elevated erythrocyte sedimentation rate (ESR). Initial electrocardiogram showed sinus tachycardia without conduction abnormalities. Echocardiography performed during the acute phase was essential for baseline assessment and monitoring. The patient received timely administration of high-dose intravenous immunoglobulin (IVIG) (2 g/kg) and high-dose aspirin within the optimal treatment window. Conclusion: This case underscores the paramount importance of early clinical recognition based on established criteria and prompt initiation of IVIG therapy in mitigating the risk of CAA in children with KD. Despite successful treatment in this instance, the challenges of underdiagnosis and variable clinical presentations, including incomplete forms, persist globally, particularly in regions like Indonesia. Continued research into KD pathogenesis, improved diagnostic markers, management of IVIG resistance, and long-term cardiovascular surveillance protocols are crucial for optimizing patient outcomes.